1985
DOI: 10.1111/j.1600-0528.1985.tb01676.x
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Sherbrooke‐Lac Megantic fluoride varnish study after 20 months

Abstract: The purpose of this study was to demonstrate the effectiveness of two fluoride varnishes (Duraphat and Fluor Protector) in the prevention of dental caries in children residing in a non-fluoridated community. At baseline, 787 grade one children (6-7-yr old) were examined and randomly allocated into a control and two treatment groups. At 20 months, 703 children remained in the study. The mean baseline caries experience and the mean number of permanent teeth present at 20 months were not significantly different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…There were six randomized 11-13,15-19 and two nonrandomized 20,21 clinical trials concerning the primary dentition, 11 randomized 11-13,22-32 and two nonrandomized 33,34 clinical trials concerning the permanent dentition and one controlled 35 clinical trial that combined results for both dentitions. The interventions for the control groups were no treatment, oral health counseling or placebo varnish.…”
Section: Discussion Of Evidence and Clinical Recommendationsmentioning
confidence: 99%
“…There were six randomized 11-13,15-19 and two nonrandomized 20,21 clinical trials concerning the primary dentition, 11 randomized 11-13,22-32 and two nonrandomized 33,34 clinical trials concerning the permanent dentition and one controlled 35 clinical trial that combined results for both dentitions. The interventions for the control groups were no treatment, oral health counseling or placebo varnish.…”
Section: Discussion Of Evidence and Clinical Recommendationsmentioning
confidence: 99%
“…The efficacy of topical fluorides in general and fluoride varnishes in particular in reducing dental caries has been extensively documented [2, 1618]. Since the advent of the first varnishes, researchers have strived to improve both efficacy and delivery of fluorides in varnishes [3, 10, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Tactile examinations, with radiographs, found caries reductions of 56% in the occlusal fissures of first permanent molars following biannual applications of Duraphat and quarterly examinations. Other randomised clinical trials [Clark et al, 1985;Tewari, 1990, Bravo, 1997] also showed reduced levels of caries of 25-73% following twice-yearly Duraphat applications. These were typical of the studies included in the Cochrane review undertaken by Marinho [2002].…”
Section: Discussionmentioning
confidence: 99%